Prevalence of tool behaviour is associated with pelage phenotype in intraspecific hybrid long-tailed macaques (Macaca fascicularis aurea × M. f. fascicularis) - Gumert, Michael David (2019)
Stone-hammering behaviour customarily occurs in Burmese long-tailed macaques, Macaca fascicularis aurea, and in some Burmese-common longtail hybrids, M. f. aurea × M. f. fascicularis; however, it is not observed in common longtails. Facial pelage discriminates these subspecies, and hybrids express variable patterns. It was tested if stone hammering related to facial pelage in 48 hybrid longtails, across two phenotypes — hybrid-like (N=19) and common-like (N=29). In both phenotypes, tool users showed similar frequency and proficiency of stone hammering; however, common-like phenotypes showed significantly fewer tool users (42%) than hybrid-like phenotypes (76%). 111 Burmese longtails showed the highest prevalence of tool users (88%). Hybrid longtails living together in a shared social and ecological environment showed a significant difference in tool user prevalence based on facial pelage phenotype. This is consistent with inherited factors accounting for the difference, and thus could indicate Burmese longtails carry developmental biases for their tool behaviour.